Dosimetric evaluation of 3D-printed polylactic acid (PLA) anthropomorphic radiotherapy head phantom using Gafchromic EBT-XD films, OSLD Nanodot and TLD-100 (penilaian dosimetrik kepala fantom radioterapi antropomorfik asid polilaktik bercetak 3D (PLA) menggunakan filem Gafchromic EBT-XD, OSLD Nanodot dan TLD-100) - Talik Sisin, Noor Nabilah; Mohd Zain, Nur Emirah; Isamail, Nor Arina; Abdullah, Reduan; Khairil Anuar, Muhammad Afiq; Mohd Zainudin, Nur Hamizah; Abdul Kadir, Ahmad Bazlie; Abd Rahni, Ashrani Aizzuddin; Rahman, Wan Nordiana; Almutery, Aml; Abd Rashid, Raizulnasuha (Penerbit Universiti Kebangsaan Malaysia, 2025)
Recently, additive manufacturing or 3-dimensional (3D) printing has been utilized to create low-cost and customized radiotherapy phantoms for quality assurance and radiation dosimetry. In this study, the head phantom was fabricated by scanning a standard RANDO® head phantom using a Kinect® Xbox 360® and printed using polylactic acid (PLA) with 100% infill. The 3D-printed anthropomorphic head phantoms underwent CT simulation, treatment planning, and treatment delivery, similar to the patient setup in radiotherapy with a whole brain target. Irradiation of the phantoms were delivered with a single fraction of 400 cGy using 6 MV photon beam energy. The absorbed dose was measured with three dosimeters: GafChromic EBT-XD film, TLD-100, and OSLD NanoDot. Gamma analysis of EBT-XD films indicated a 30% dose difference for the irradiation’s pass rate of 3D printed head phantom and RANDO® phantom compare to TPS dose calculation. TLD’s measurement of the 3D printed phantom resulted in 99% similarity to the TPS calculation and RANDO® phantom TLD’s results. Meanwhile, the percentage dose difference between OSLD reading of 3D printed phantom and TPS calculation was 8.1%. Therefore, this study demonstrates the feasibility of the 3D-printed head RP as an alternative phantom to RANDO® head RP. Further improvement in the phantom design details might enhance the dosimetry outcome and accuracy.